Research on underwater wireless dynamic optical communication system based on PPM modulation - Dong, Bing; Tong, Shoufeng; Zhang, Peng; Wang, Jiaxing (Frontiers in Physics, 2023)
In order to achieve underwater wireless dynamic optical communication, a laser communication system based on PPM modulation is proposed. In order to accurately and objectively describe the mechanism of underwater laser communication, a mathematical model of underwater laser communication based on small angle analysis was constructed. The PPM demodulation algorithm is designed, and the workflow of modulation and demodulation in the transmit module and the receive module is given. In the experiment, Lumileds-470nm light source was selected for data communication testing at a communication rate of 15 Mbp/s. In the servo control process, the square wave signal used for stepping motor drive has a stable amplitude output and a stable time width. It can well simulate the testing process of underwater dynamic scanning. The experimental results obtained laser light spots under different attenuation states, analyzed the characteristics of the light spot distribution, and completed the numerical reconstruction of the light spot energy in MATLAB. Three types of light attenuators, 1.0%, 0.1%, and 0.01%, were used to simulate different light attenuations underwater. The test results show that the system error rate is better than 10-6 when using 1.0% attenuation chips. When using a 0.1% attenuation chip, the error rate of the system is reduced to 10-4. When using a 0.01% attenuation patch, the system cannot obtain a valid signal. The feasibility of the system is verified.